2005
DOI: 10.1007/s10741-005-5252-6
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomeric Protein Mutations in Dilated Cardiomyopathy

Abstract: This review aims to provide a concise summary of the DCM associated mutations identified in the proteins of the sarcomere and cytoskeleton, and discuss the reported effects of the mutations, as determined by functional studies, and in relation to the known structure of the protein affected. The mechanisms by which single missense mutations in the proteins of the sarcomere can lead to similar diseases as those caused by mutations in the proteins of the sarcolemma and cytoskeleton, are still unknown. However, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(108 citation statements)
references
References 70 publications
4
102
1
1
Order By: Relevance
“…66 Therefore, sarcomere mutations can be found in both HCM and DCM, but difference in the functional alterations may determine the different phenotypes. 67 …”
Section: Sarcomere Mutations In Dcmmentioning
confidence: 99%
“…66 Therefore, sarcomere mutations can be found in both HCM and DCM, but difference in the functional alterations may determine the different phenotypes. 67 …”
Section: Sarcomere Mutations In Dcmmentioning
confidence: 99%
“…TNNT2 is a sarcomeric protein important for proper contraction of cardiomyocytes. In humans, mutations in TNNT2 have been found in patients with late-onset dilated cardiomyopathy 55 which, similarly to mutations in dystrophin, may create predisposition to enteroviral infection and consequent tissue damage. Vms3 on chromosome 4 is bound within a much smaller locus, containing 109 genes.…”
Section: Genetic Control Of Viral Myocarditis In Micementioning
confidence: 99%
“…Epidemiological studies addressing the prevalence of gene mutations in DCM patients have demonstrated that inherited forms account for at least one-third of all DCM cases. [1][2][3][4] Familial cases frequently show a monogenic origin, and transmission indicates autosomal dominant or X-linked inheritance pattern with incomplete and age-dependent penetrance. 3 To date, positional cloning and candidate gene screening have led to the identification of numerous heterozygous mutations in more than 40 different genes, most of which encode proteins important for the structural integrity and function of cardiomyocytes, such as regulatory proteins of the sarcomere, the nuclear envelope or intracellular homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…3 To date, positional cloning and candidate gene screening have led to the identification of numerous heterozygous mutations in more than 40 different genes, most of which encode proteins important for the structural integrity and function of cardiomyocytes, such as regulatory proteins of the sarcomere, the nuclear envelope or intracellular homeostasis. 1,2,5 In particular, defects in proteins required for force transduction and force transmission of the sarcomeric apparatus seem to promote the development of DCM.…”
Section: Introductionmentioning
confidence: 99%